Modelling of solar micro gas turbine for parabolic dish based controller application - Syariffah Othman; Mohd Ruddin Ab. Ghani; Zanariah Jano; Tole Sutikno (Universitas Ahmad Dahlan, 2020)
Dish-Stirling unit and photovoltaic panels are the premier technologies available to generate off-grid solar energy. The major issue for both systems is in terms of producing output power. Air-Brayton cycle was utilized asan engine by converting the thermal energy to electricity. Micro gas turbine (MGT) has been recognized as one of the viable alternatives compared to Stirling engines, where it represents a state-of-art parabolic dish engine specifically in turbine gas technology. Hence, the microgas turbine is a technology that is capable of controlling low carbon while providing electricity in off-grid regions. MGT uses any gas as its input like natural gas, bio gas and others. Micro gas turbine has advantages for its high expansion ratio and less moving components. Compared to competing for diesel generators, the electricity costs from hybrid solar units were reduced between 10% and 43%, where as specific CO2 emissions reduced by 20-35%. MGT provides advantages over photovoltaic systems such as the inherent ability to hybridize the systems with hydrocarbon fuels to produce electricity around the clock, and the ability to operate more effectively in very hot climates with photovoltaic performance degradation over the life time of the system. Hybrid solar micro gas-turbines are cost-effective, eco-friendly and pollution free as they can work by burning any gas like natural gas,landfill gasa and others.This paper presented the controls contained in the MGT-dish system consisted of temperature control, fuel flow control, speed and acceleration control. Aconceptual design of the 25kW MGT-dish system was also covered.